Evaluation of olanzapine pamoate depot in seriously violent males with schizophrenia in the community. (October 2016) - Kasinathan, John; Sharp, Gillian; Barker, Anthony
Objectives: Olanzapine is a well established treatment for schizophrenia. The olanzapine pamoate depot (long-acting injectable) formulation improves compliance and clinical trials have shown it to be effective. However, there are no previously published reports evaluating olanzapine depot in violent patients with schizophrenia in the community. We evaluated the clinical efficacy of olanzapine depot, its effect on violence, hospitalization and incarceration in community patients with schizophrenia and prior history of serious violence. Methods: This was a retrospective service evaluation in a community forensic psychiatry service where patients had schizophrenia spectrum disorder and a significant history of violence. Treatment resistance, substance use disorders and antisocial personality disorder were common. Nine deidentified patient records were audited for 12 months pre and 12 months post olanzapine depot initiation to identify any clinical changes, breaches of (legislated) psychiatric treatment orders, hospital admission days, days incarcerated and emergency presentations. Results: Community forensic psychiatric patients treated with olanzapine depot showed an improvement in psychotic symptoms ( p = 0.008) with overall decreases in violence, supported by reductions in hospitalization days ( p = 0.018) and days incarcerated ( p = 0.043). Several patients had reduced psychiatric treatment order breaches and emergency presentations. Conclusions: Community forensic psychiatric patients with schizophrenia responded to olanzapine depot with decreased violence and reduced hostility. A depot antipsychotic medication that reduces violence and improves engagement has significant implications for greater effective community management of forensic patients with schizophrenia.